2014
DOI: 10.4103/2230-8598.137719
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting home delivery among women in Bosomtwe-Atwima-Kwanwoma district of Ghana: A case control study

Abstract: Background: Maternal mortality is unacceptably high in Ghana. This situation is attributed partly to non-availability of healthcare services and poor utilization of these services when they are available. More deliveries are still performed at home, and in many cases, without the supervision of trained attendants, despite the Ghana Government's fee exemption policy on maternal deliveries. The purpose of this study was to identify factors that predict home delivery among mothers. Materials and Methods: An unmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
2
5
1
Order By: Relevance
“…Maternal age has been linked to parity and various aspects of life [29], realising that older women have higher propensity of home delivery may be due to negative experiences during previous deliveries in health facilities such as attitude of care providers [30]. This observation might also be due to the thought that they have much experience as far as delivery is concerned and therefore there is no need to seek SBA or health facility.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal age has been linked to parity and various aspects of life [29], realising that older women have higher propensity of home delivery may be due to negative experiences during previous deliveries in health facilities such as attitude of care providers [30]. This observation might also be due to the thought that they have much experience as far as delivery is concerned and therefore there is no need to seek SBA or health facility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating factors associated with place of delivery, reported age of the mother as one of risk factor associated with home delivery [ 13 16 ]. In the univariate analysis, both age of the mother and that of the partner were associated with the risk of home delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated using the Epi Info version 7 software program by considering 80% power, 95% confidence level, 10% nonresponse rate, a1 : 2 case to control ratio, and taking exposure factors from different studies [ 12 14 ]. The sample size was 264 (88 cases and 176 controls).…”
Section: Methodsmentioning
confidence: 99%
“…Face to face interview technique was used to collect data by making house to house visit. The questionnaire was adapted from different literatures and Ethiopian Demographic and Health Survey (EDHS) [ 5 , 12 , 14 ]. Data were collected by using seven trained diploma nurses.…”
Section: Methodsmentioning
confidence: 99%